Farmers’ trust in government and participation intention toward rural tourism through TAM: The moderation effect of perceived risk - Yu, Xia (Frontiers in Psychology, 2022)
The farm and farmers in China are highly associated with the steadiness and development of the country and even the world. Farmers are the main subjects in rural development and play a vital role in the reception, management, and benefit distribution in rural tourism activities during the development of rural tourism. Farmers’ perception and participation intention in rural tourism development are directly related to the sustainable development of rural tourism and the realization of rural revitalization goals. The decision-making process of participation in the rural tourism development fits the application conditions of the technology acceptance model (TAM) . Therefore, in order to explore the influencing factors of farmers’ decision-making process in participating in the rural tourism, this study employs the technology acceptance model to predict and judge individual farmers' willingness and behavior to participate in the rural tourism. The government trust and perceived risk in the real problem of low participation of farmers in the rural tourism development are considered. Then, an extended technology acceptance model was established by taking 409 farm households as research samples. The influence of government trust on farmers' participation intention in the rural tourism was empirically analyzed based on the PLS-SEM model. The results show that farmers' perceived usefulness and perceived ease of use in rural tourism affect their participation intention. Farmers' judgments on whether governments can assume public responsibilities and achieve public interests through rural tourism development affects their trust in government, while the government trust can positively affect farmers' participation intention via perceived usefulness and perceived ease of use. This indicates that government trust is an important antecedent variable influencing farmers' participation in the rural tourism. The perceived risk affects farmers' perceived usefulness and participation intention in the rural tourism, and plays a moderating role in the relationship between government trust and perceived usefulness. Finally, this study recommends to highlight the utility and convenience of rural tourism participation during the promotion of farmers' participation in rural tourism development, enhance the ability of farmers to participate in rural tourism development, and choose multiple channels to increase government trust to reduce farmers' risk concerns.